Temporal evolution of plutonium concentrations and isotopic ratios in the Ukedo - Takase Rivers draining the Difficult-To-Return zone in Fukushima, Japan (2013–2020). (15th February 2023) - Diacre, Aurélie; Chalaux Clergue, Thomas; Burban, Soazig; Gauthier, Caroline; Hubert, Amélie; Humbert, Anne-Claire; Lefevre, Irène; Fauré, Anne-Laure; Pointurier, Fabien; Evrard, Olivier
Abstract: In 2011, the Fukushima Dai-Ichi Nuclear Power Plant (FDNPP) accident released significant quantities of radionuclides into the environment. Japanese authorities decided to progressively reopen the Difficult-To-Return Zone after the decontamination of priority reconstruction zones. These areas include parts of the initially highly contaminated municipalities located to the north of the FDNPP, including Namie Town, an area drained by the Ukedo and Takase Rivers. Eleven years after the accident, research focused on the spatial distribution of plutonium (Pu) and radiocesium (Cs) isotopes at contrasted individual locations. To complement previous results, the current research was conducted on flood sediment deposits collected at the same locations after major flooding events during eleven fieldwork campaigns organised between 2013 and 2020 at the outlet of the Ukedo and Takase Rivers (n = 22). The results highlighted a global decrease of the Pu and 137 Cs contents in sediment with time during the abandonment phase in the region, from 2013 (238.20 fg g −1 ) to 2020 (4.28 fg g −1 ). Furthermore, based on the analysis of the 240 Pu/ 239 Pu isotopic ratios, the plutonium transiting these rivers (range: 0.166 – 0.220) essentially originated from the global fallout (0.180 ± 0.014 (Kelley et al., 1999)). Sediment showed contrasted properties in the two investigated rivers, which is likely mainly the result of the occurrence of Ogaki Dam on upper sections of the Ukedo River as it strongly impacts the material supply from this river to the Pacific Ocean. A statistical analysis highlighted the strong correlation between Pu activity concentrations and 137 Cs activities in both rivers, confirming that both radionuclides are transported with a similar pathway. Despite it was detected early after the accident (2011–2013), the current research demonstrates that plutonium originating from FDNPP is no longer detected in these rivers draining the Difficult-To-Return Zone at the onset of the reopening of the area to its former inhabitants. Graphical abstract: Image 1 Highlights: Radionuclides analysed in sediment from two rivers draining Fukushima plume. Global decrease of both Pu and 137 Cs contents in sediment from 2013 to 2020. The plutonium now exclusively originates from global fallout. Plutonium is transported with a similar pathway as radiocesium. The Ogaki dam on the Ukedo River highly impacted the radionuclide transfer.